Relaxation dynamics and polydispersivity associated with defects and ferroelectric correlations in Ba-doped EuTiO3. (20th October 2017) - Iqbal, Asad M; Jaffari, Ghulam Hassnain; Saleemi, Mohsin; Ceylan, Abdullah
Abstract: We present the frequency- and temperature-dependent dielectric response of Eu1− x Ba x TiO3 (0 ⩽ x ⩽ 0.5) in detail. Excluding grain boundary effects, four relaxation mechanisms were observed. Relaxation dynamics were observed to arise due to hopping conduction associated with defects, namely oxygen vacancies as well as Eu 3+ and Ti 3+ ions. Dielectric relaxation analysis led to the identification of Ti ions in two different environments with different relaxation rates in the overall EuTiO3 perovskite structure. The emergence of another relaxation mechanism associated with ferroelectric order as a consequence of the formation of polar regions was also observed for higher Ba concentrations. The addition of Ba led to the identification of relaxation dynamics associated with hopping conduction between Eu ions, Ti ions (in the regions with and without oxygen vacancies) and with the formation of ferroelectric polar regions. Furthermore, the polydispersivity and relaxation times were extracted within the framework of the modified Debye model. Relaxation times have been observed to increase with a decrease in temperature while larger values of polydispersivity reveal a wide distribution of relaxation times due to the presence of lattice parameter and energy barrier distributions.